2021
DOI: 10.1108/ijph-12-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of perceived stress and control of anger, anxiety and depression of people staying in Polish penitentiary institutions

Abstract: Purpose The purpose of this study is to assess the intensity of perceived stress and measure the subjective control of anxiety, anger and depression in a group of women and men staying in Polish penitentiary institutions. Design/methodology/approach The research was carried out in two penitentiary institutions located in the Lesser Poland Voivodeship at the turn of 2019/2020. The study group consisted of 152 prisoners. In the cross-sectional study, two standardised research tools – the Perceived Stress Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…According to our findings, 75%, 38.3%, and 36.7% of individuals, respectively, exhibited mild to extremely severe stress, anxiety, and depression symptoms. Recently published studies found that being incarcerated is consistently related to an increased risk of poor mental health [ 41 , 42 ]. Furthermore, we found higher levels of depression and anxiety than those indicated by research on depression worldwide – where depression was 33.7%, and anxiety was 31.9% [ 43 ]—and lower than among Iranian and Ethiopian prisoners, where depression varied between 44% and 66.4% and anxiety between 56.3% and 66.9% [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our findings, 75%, 38.3%, and 36.7% of individuals, respectively, exhibited mild to extremely severe stress, anxiety, and depression symptoms. Recently published studies found that being incarcerated is consistently related to an increased risk of poor mental health [ 41 , 42 ]. Furthermore, we found higher levels of depression and anxiety than those indicated by research on depression worldwide – where depression was 33.7%, and anxiety was 31.9% [ 43 ]—and lower than among Iranian and Ethiopian prisoners, where depression varied between 44% and 66.4% and anxiety between 56.3% and 66.9% [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, when inmates enter the penal system and serve their sentences, they should be screened for mental health disorders on a regular basis [ 21 ]. Third, this study may help develop psychotherapeutic programs to evaluate how the incarcerated might best cope with stress and manage emotions [ 41 ]. In terms of therapeutic approaches, cognitive-behavioral techniques (e.g., cognitive restructuring) may be beneficial by lowering negative thoughts, worry, and anxiety, which in turn may lead to excessive fears.…”
Section: Discussionmentioning
confidence: 99%
“…No one will be surprised if we affirm that the prison environment and serving a prison sentence is not a situation comparable to life outside prison, due to the inherent restrictions of freedom and institutionalized control prisoners experience. In addition, it can cause considerable levels of stress on the individual ( Kołodziej et al, 2021 ). An interesting question is whether this can affect the effectiveness of immersive VR sessions.…”
Section: Influence Of Contextual Factors On Personal Experience Insid...mentioning
confidence: 99%